Scapular upward rotation during passive humeral abduction in individuals with hemiplegia post-stroke - Jonjin Ratanapinunchai (2019)
© 2019 by Korean Academy of Rehabilitation Medicine. Objective To describe scapular upward rotation during passive humeral abduction in individuals with hemiplegia post-stroke compared to normal subjects. Methods Twenty-five individuals with hemiplegia post-stroke and 25 age- and gender-matched normal subjects voluntarily participated in this study. Scapular upward rotation during resting and passive humeral abduction at 30°, 60°, 90°, 120°, and 150° were measured using a digital inclinometer. Results In both groups, scapular upward rotation significantly increased as humeral abduction increased (p < 0.001). Scapular upward rotation was significantly less in the hemiplegic group compared to that in the control at 90° (p=0.002), 120° (p < 0.001), and 150° of humeral abduction (p < 0.001). The mean difference in scapular upward rotation between these two groups ranged from 6.3° to 11.38°. Conclusion Passive humeral abductions ranging from 90° to 150° can significantly alter scapular upward rotation in individuals with hemiplegia post-stroke compared to those of matched normal subjects. The magnitude of reduction of the scapular upward rotation may potentially lead to the development of hemiplegic shoulder pain after prolonged repetitive passive movement. Scapular upward rotation should be incorporated during passive humeral abduction in individuals with hemiplegia post-stroke, especially when the humeral is moved beyond 90° of humeral abduction. Combined movements of scapular and humeral will help maintain the relative movement between the scapula and humerus. However, further longitudinal study in patients with shoulder pain post-stroke is needed to confirm these findings.